Rapid Assembly of Multiple-Exon cDNA Directly from Genomic DNA - An, Xiaoping (Public Library of Science, 2007)
BACKGROUND: Polymerase chain reaction (PCR) is extensively applied in gene cloning. But due to the existence of introns, low copy number of particular genes and high complexity of the eukaryotic genome, it is usually impossible to amplify and clone a gene as a full-length sequence directly from the genome by ordinary PCR based techniques. Cloning of cDNA instead of genomic DNA involves multiple steps: harvest of tissues that express the gene of interest, RNA isolation, cDNA synthesis (reverse transcription), and PCR amplification. To simplify the cloning procedures and avoid the problems caused by ubiquitously distributed durable RNases, we have developed a novel strategy allowing the cloning of any cDNA or open reading frame (ORF) with wild type sequence in any spliced form from a single genomic DNA preparation. METHODOLOGY: Our “Genomic DNA Splicing” technique contains the following steps: first, all exons of the gene are amplified from a genomic DNA preparation, using software-optimized, highly efficient primers residing in flanking introns. Next, the tissue-specific exon sequences are assembled into one full-length sequence by overlapping PCR with deliberately designed primers located at the splicing sites. Finally, software-optimized outmost primers are exploited for efficient amplification of the assembled full-length products. CONCLUSIONS: The “Genomic DNA Splicing” protocol avoids RNA preparation and reverse transcription steps, and the entire assembly process can be finished within hours. Since genomic DNA is more stable than RNA, it may be a more practical cloning strategy for many genes, especially the ones that are very large and difficult to generate a full length cDNA using oligo-dT primed reverse transcription. With this technique, we successfully cloned the full-length wild type coding sequence of human polymeric immunoglobulin receptor, which is 2295 bp in length and composed of 10 exons.